2022
DOI: 10.1186/s13062-022-00328-8
|View full text |Cite
|
Sign up to set email alerts
|

Intron losses and gains in the nematodes

Abstract: Background The evolution of spliceosomal introns has been widely studied among various eukaryotic groups. Researchers nearly reached the consensuses on the pattern and the mechanisms of intron losses and gains across eukaryotes. However, according to previous studies that analyzed a few genes or genomes, Nematoda seems to be an eccentric group. Results Taking advantage of the recent accumulation of sequenced genomes, we extensively analyzed the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 89 publications
2
9
0
Order By: Relevance
“…A positive correlation was observed between the BUSCO score and both genome N50 (Kendall's τ = 0.49, P = 0.01) and ONT coverage (Kendall's τ = 0.44, P = 0.02). The intron distribution of the Dorylaimia and Chromadoria lineages sequenced in this study had a similar pattern, peaking around 55 bp (Table 2 ; Supplementary Figure S9 ), and were similar to previously published nematodes in these clades ( 74 ). Interestingly, there are fewer but longer introns in the four Enoplia species, suggesting a different intron distribution in the last common ancestor of this clade compared with the rest of the nematodes (Figure 3B ; Supplementary Figure S10 ).…”
Section: Resultssupporting
confidence: 86%
“…A positive correlation was observed between the BUSCO score and both genome N50 (Kendall's τ = 0.49, P = 0.01) and ONT coverage (Kendall's τ = 0.44, P = 0.02). The intron distribution of the Dorylaimia and Chromadoria lineages sequenced in this study had a similar pattern, peaking around 55 bp (Table 2 ; Supplementary Figure S9 ), and were similar to previously published nematodes in these clades ( 74 ). Interestingly, there are fewer but longer introns in the four Enoplia species, suggesting a different intron distribution in the last common ancestor of this clade compared with the rest of the nematodes (Figure 3B ; Supplementary Figure S10 ).…”
Section: Resultssupporting
confidence: 86%
“…Using the MAKER pipeline, 22,422 -59,888 protein-coding genes were annotated in 13 free-living nematode genomes and were 34.5 to 92.6% complete based on BUSCO analysis (Supplementary Table S10). The intron distribution of the Dorylaimia and Chromadoria lineages sequenced in this study had a similar pattern, peaking around 50 bp (Table 2, Supplementary Figure S7) and were similar to previously published nematodes in these clades (77). Interestingly, there are fewer but longer introns in the four Enoplia species, suggesting a different intron distribution in the last common ancestor of this clade compared to the rest of nematodes (Figure 3B, Supplementary Figure S8).…”
Section: Genome Characteristics Of Free-living Nemtodessupporting
confidence: 85%
“…6B), and 64.3% of the 167,873 introns from single-copy orthologs are unique. While several previous studies have demonstrated a high rate of intron loss in nematodes (Kent and Zahler 2000; Cho et al 2004; Kiontke et al 2004; Coghlan and Wolfe 2004), others focusing on highly conservative genes have reported much higher level of conservation in exon/intron structure (Ma et al 2022). Our work, which includes a small set of species that have nearly complete genomes, reveals very low levels of gene structure conservation, and that even within an examination of a small fraction of known Clade V nematodes.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, Caenorhabditis nematodes display a relatively high rate of gene turnover, involving both the expansion and reduction of gene families (Fierst et al 2015; Adams et al 2023; Ma et al 2024). Moreover, the exon/intron structure in orthologous genes in nematodes is not conservative, particularly via the substantial loss of introns (Kent and Zahler 2000; Cho et al 2004; Kiontke et al 2004; Coghlan and Wolfe 2004; Ma et al 2022).…”
Section: Introductionmentioning
confidence: 99%